The Effect of Training Method and Educability on Karate-Kata Skill - Aisyah, Siti; Muhtar, Tatang; Yudiana, Yunyun (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
This study was aimed at examining the effect of whole part hole training method and whole training method on the karate-kata skill of the students with high motor educability and low motor educability who joined Karate extracurricular. The method used was the ex post facto method with factorial design 2x2. The samples of the study were 80 elementary school students joining Karate extracurricular in SDIT Darul Ma’arif, Bandung Districts. The training was conducted twice a week for 20 weeks. The test instrument used was the karate-kata Heian Shodan test instrument. The obtained data were analyzed by MS Excel 2010 software with two-way Anova test. The results of the study show that: the whole part whole training method has a better impact on the karate-kata skill than the whole training method; the karate-kata skill of the high motor educability group was better than the low motor educability group; there was no interaction between the training method and motor educability on the mastery of karate-kata skill. According to the result of the study, it concludes that the whole part whole training method is more effective that the whole training method, while a high motor educability is better than the low motor educability.